Gender equality with regard to the current challenges to Ukraine’s national security: theoretical and practical aspects - Yu. O. Zahumenna; D. P. Hrelya (Law and Safety)
The article examines the legal and institutional mechanisms for integrating gender equality into the national security and defence sector of Ukraine. The analysis of the legal framework governing gender policy, in particular in the Armed Forces of Ukraine, is carried out. Particular attention is paid to the role of international standards, such as UN Security Council Resolution 1325 and the Istanbul Convention, in ensuring equal access of women and men to participation in defence processes.